ANALISIS PERAN ORANG TUA DALAM MEMOTIVASI SISWA BELAJAR PADA MASA PANDEMI COVID-19 - Kamila, Cahya; S. Putra, Karantiano (Pendidikan Guru Sekolah Dasar Institut Pendidikan Indonesia Garut, 2022)
This research is a qualitative research using qualitative descriptive research. Participants in this study consisted of 20 students and 4 parents. The selection of subjects in this study was carried out by using purposive sampling technique. Data collection techniques in this study used questionnaires, interviews and documentation. The results of the study showed that the motivation of students to learn online during the Covid-19 pandemic was included in the good category. Whereas from the results of data processing, 20 of them obtained 4 students with very good criteria (81%), 14 students with good criteria (61%), and 2 students with sufficient criteria (41%). The role of parents in motivating students to learn online is in the good category. This can be seen from good parental education that can help when students experience learning difficulties. Parents' work affects the family economy and with a good job it will get a good income so that it supports student learning facilities.